Personal sustainability exploring the far side of sustainable development - Parodi, Oliver; Tamm, Kaidi (Routledge, Taylor & Francis Group, 2019)
Transition to sustainability is stuck and academic research has not resulted in significant change so far. A large void in sustainability research and the understanding of sustainable development is an important reason for this. Personal Sustainability seeks to address this void, opening up a whole cosmos of sustainable development that has so far been largely unexplored. Mainstream academic, economic and political sustainable development concepts and efforts draw on the macro level and tend to address external, collective and global processes. By contrast, the human, individual, intra- and inter-personal aspects on the micro level are often left unaddressed
Includes bibliographical references and index
Keywords: Sozialökologie; Nachhaltigkeit; Person; Humanökologie; Lebensstil; Sozialer Wandel; Sustainable development / Philosophy; Sustainable development / Psychological aspects; Social change; Human ecology; Sustainable development; Aufsatzsammlung